2005
DOI: 10.1017/s0954579405050522
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, autonomic, and serotonergic correlates of parasuicide among adolescent girls

Abstract: Although parasuicidal behavior in adolescence is poorly understood, evidence suggests that it may be a developmental precursor of borderline personality disorder~BPD!. Current theories of both parasuicide and BPD suggest that emotion dysregulation is the primary precipitant of self-injury, which serves to dampen overwhelmingly negative affect. To date, however, no studies have assessed endophenotypic markers of emotional responding among parasuicidal adolescents. In the present study, we compare parasuicidal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
193
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 183 publications
(218 citation statements)
references
References 140 publications
(78 reference statements)
24
193
1
Order By: Relevance
“…In the present context, it is possible that sadness cues are not eliciting active avoidance motivations among children with DBDs. Again, this conjecture is speculative and requires further study.Prediction of internalizing symptoms by deficits in response coherence between facial sadness and RSA is consistent with a growing literature linking vagal deficiencies to depressive, anxious, and self-injurious behaviors (e.g., Crowell et al 2005;Rottenberg, Salomon, Gross, & Gotlib, 2005;Thayer, Friedman, & Borkovec, 1996). Yet reduced RSA is also observed consistently among externalizing children and adolescents (Beauchaine et al, , 2007Mezzacappa et al, 1997).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…In the present context, it is possible that sadness cues are not eliciting active avoidance motivations among children with DBDs. Again, this conjecture is speculative and requires further study.Prediction of internalizing symptoms by deficits in response coherence between facial sadness and RSA is consistent with a growing literature linking vagal deficiencies to depressive, anxious, and self-injurious behaviors (e.g., Crowell et al 2005;Rottenberg, Salomon, Gross, & Gotlib, 2005;Thayer, Friedman, & Borkovec, 1996). Yet reduced RSA is also observed consistently among externalizing children and adolescents (Beauchaine et al, , 2007Mezzacappa et al, 1997).…”
supporting
confidence: 85%
“…However, several previous studies have demonstrated the effectiveness of the The Champ in evoking state sadness (Crowell et al, 2005;Goldin et al, 2005;Gross & Levenson, 1995;Hewig et al, 2005;Hutcherson et al, 2005). Furthermore, even though group differences in facial expressions and autonomic reactivity were not observed during the film, both groups demonstrated increased …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…withdrawal to emotion evocation correlate with symptoms of both internalizing and externalizing psychopathology (see Beauchaine, 2001Beauchaine, , 2012Porges, 2007;Vasilev, Crowell, Beauchaine, Mead, & GatzkeKopp, 2009), and with a wide range of psychopathological outcomes, including anxiety (e.g., Hastings et al, 2008;Kemp et al, 2014;Thayer, Friedman, & Borkovec, 1996), phobias (e.g., Å hs, Sollers, Furmark, Fredrikson, & Thayer, 2009), attention problems (see Rash & Aguirre-Camacho, 2012), autism (Neuhaus, Bernier, & Beauchaine, 2014;Patriquin, Scarpa, Friedman, & Porges, 2013), callousness (de Wied, van Boxtel, Matthys, & Meeus, 2012), conduct disorder Beauchaine, Katkin, Strassberg, & Snarr, 2001), depression (e.g., Rottenberg, 2007;Rottenberg, Salomon, Gross, & Gotlib, 2005;Rottenberg, Wilhelm, Gross, & Gotlib, 2002), nonsuicidal self-injury (Crowell et al, 2005), panic disorder (e.g., Asmundson & Stein, 1994), trait hostility (Sloan et al, 1994), psychopathy (Hansen, Johnsen, Thornton, Waage, & Thayer, 2007), and schizophrenia (Clamor, Lincoln, Thayer, & Koenig, in press). 5 Moreover, comorbid internalizing and externalizing symptoms predict greater RSA withdrawal to emotion evocation than either internalizing or externalizing symptoms alone (Calkins, Graziano, & Keane, 2007;Pang & Beauchaine, 2013).…”
Section: Emotion Dysregulation and Youth Psychopathologymentioning
confidence: 99%
“…The invitation included a $25 monetary incentive. The study was approved by the Seattle Children's Hospital and Regional Medical Center Institutional Review Board, and all participants and their mothers provided written informed assent and consent, respectively.The sample described herein includes a different but overlapping set of the participants described by Crowell et al (2005). This is because some participants declined further participation in the discussion task, which has not been reported previously, and because the present sample includes 4 male participants (2 in each group) who were excluded from previous analyses.…”
mentioning
confidence: 99%